The Effect of Immediate Functional Ankle Rehabilitation on a Range of Motion, Muscle Strength, and Stiffness after Achilles Tendon Repair in Soccer Player - Kwang-Jin Lee; Se-Young Seon; Byoung-Jae Park; Keun-Ok An (The Asian Journal of Kinesiology, 2023)
PURPOSE This study aims to investigate the effect of immediate functional ankle rehabilitation after Achilles tendon repair on an ankle range of motion, muscle strength, and stiffness in soccer players. METHODS The subject of this case study is one soccer player belonging to team A. Athlete A (age 25 years, height 174 cm, weight 63 kg) visited hospital B due to an Achilles tendon rupture that occurred during the training in February 07, 2022. February 08, 2022, athlete A had Achilles tendon reconstruction at B hospital. Two weeks after the operation, athlete A visited the M exercise center and performed immediate functional rehabilitation exercises for 16 weeks. RESULTS As a result of 16 weeks of immediate functional ankle rehabilitation exercise, athlete A’s ankle joint range of motion (supine and prone dorsi flexion, supine and prone plantar flexion), muscle strength (supine and prone dorsi flexion, supine and prone plantar flexion, inversion, eversion), and stiffness(Achilles tendon, gastrocnemius medial and lateral) were positively improved. Also, the difference between the range of motion, muscle strength, and stiffness of the affected involved and noninvolved side of the ankle was decreased after 8 and 16 weeks compared to pre-exercise. CONCLUSIONS Therefore, it is suggested to apply immediate functional rehabilitation exercises to help soccer players return to play early after Achilles tendon surgery.